Reduction of Cardiac Autonomic Modulation and Increased Sympathetic Activity by Heart Rate Variability in Patients With Long COVID - Marques, Karina Carvalho; Silva, Camilla Costa; Trindade, Steffany da Silva; Santos, Márcio Clementino de Souza; Rocha, Rodrigo Santiago Barbosa; Vasconcelos, Pedro Fernando da Costa; Quaresma, Juarez Antônio Simões; Falcão, Luiz Fábio Magno (Frontiers in Cardiovascular Medicine, 2022)
Several clinical manifestations of persistent long Covid have been documented; their demonstrations in the cardiovascular and autonomic nervous system in the long-term are not yet clear. Thus, we examined the presence of alterations in cardiac autonomic functioning in individuals with long-term manifestations. The study was conducted from October 2020 to May 2021, and autonomic assessment was used to collect heart rate data for heart rate variability (HRV) analysis. The study had Long Covid clinical groups (Intragroup) divided into: hospitalized; non-hospitalized; symptomatic period ≤3 months, >3 months, ≤6 months, and >6 months; with and without dyspnea and a control group (Intergroup) which were COVID-19 free. Included were those aged 23 to 59 years, 30 days after infection, and confirmed by serologic or RT-PCR (swab) diagnoses. A total of 155 patients with long Covid [95 women (61.29%) aged 43.88 ± 10.88 years and 60 men (38.71%) aged 43.93 ± 10.11 years] and 94 controls [61 women (64.89%) aged 40.83 ± 6.31 and 33 man (35.11%) aged 40.69 ± 6.35 years] were included. Intragroup comparison and intergroup revealed a reduction in global HRV, increase in sympathetic modulation, decrease in parasympathetic modulation. Sympathovagal balance in the intragroup comparison was normal and in the intergroup was reduced. Our findings indicate that Long Covid leads to sympathetic excitation and parasympathetic reduction. The excitation can increase heart rate, blood pressure and predispose to cardiovascular complications. Short-term HRV analysis showed good reproducibility to verify cardiac autonomic involvement.